Clinical Observation on Virtual Reality XBOX Gaming Combined with Routine Rehabilitation Training for Affected Upper Extremity Recovery of Stroke Patients - Junzhi ZHU; Wenheng NONG; Yingfen LIU; Shuheng ZHAO; Youhua GUO; Hongxia CHEN (康复学报)
Objective:To observe the clinical effect of virtual reality XBOX gaming and routine rehabilitation training on recovery of upper extremities'motor function of stroke patients.Methods:43 stroke patients were randomly assigned to the treatment group (n=21) and control group (n=22). The treatment group received daily routine rehabilitation training for 30 minutes and virtual reality XBOX gaming for 30 minutes; the control group received daily routine rehabilitation training for 60 minutes. Two groups received training one time each day, six times each week and lasted for two weeks. Fugl-Meyer assessment for motor function of upper extremity and Wolf motor function test were used to evaluate the affected upper extremity'motor function of patients in two groups before and after treatment.Results:Fugl-Meyer score for motor function of upper extremity and Wolf motor function test score in treatment group after two weeks'training were increased compared with those before treatment (P<0.05). The increasing amplitude of Fugl-Meyer score for motor function of upper extremity and Wolf motor function test score in treatment group after two weeks'training were higher than those of control group (P<0.05).Conclusion:Virtual reality XBOX gaming and routine rehabilitation training combination can promote the recovery of upper extremities'motor function of stroke patients, and improve their life self-care ability and life quality.